2020
DOI: 10.1186/s40560-020-0426-9
|View full text |Cite
|
Sign up to set email alerts
|

Risk modifiers of acute respiratory distress syndrome in patients with non-pulmonary sepsis: a retrospective analysis of the FORECAST study

Abstract: Background: Predisposing conditions and risk modifiers instead of causes and risk factors have recently been used as alternatives to identify patients at a risk of acute respiratory distress syndrome (ARDS). However, data regarding risk modifiers among patients with non-pulmonary sepsis is rare. Methods: We conducted a secondary analysis of the multicenter, prospective, Focused Outcomes Research in Emergency Care in Acute Respiratory Distress Syndrome, Sepsis and Trauma (FORECAST) cohort study that was conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 49 publications
2
23
1
Order By: Relevance
“…Our study found that mild TBI patients diagnosed with sepsis were drastically more likely to develop ARDS than those patients who did not exhibit sepsis (8.8% vs. 0.7%, p = 0.003). Iriyama et al showed soft tissue infection and ICU admission were the possible risk modifier of ARDS in patient with sepsis [ 21 ]. In our study, ICU admission was not noted to be a significant risk factor of sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…Our study found that mild TBI patients diagnosed with sepsis were drastically more likely to develop ARDS than those patients who did not exhibit sepsis (8.8% vs. 0.7%, p = 0.003). Iriyama et al showed soft tissue infection and ICU admission were the possible risk modifier of ARDS in patient with sepsis [ 21 ]. In our study, ICU admission was not noted to be a significant risk factor of sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, patients with Covid-19 pneumonia who develop ARDS are significantly older than those who do not (16). However, in a recent study by Iriyama et al, there was no significant difference between the mean age of patients who developed ARDS following non-pulmonary sepsis and those who did not (32). Similarly, the age of patients who developed ARDS did not vary significantly from those who did not following out-of-hospital cardiac arrest (33), neutropenia after hematologic malignancy (34), or kidney transplant (35).…”
Section: Clinical Characteristics Of Aging In Ardsmentioning
confidence: 94%
“…Ophthalmic shingles with a rash following dermatoma V1, pseudodendritic keratitis, acute hypertensive anterior uveitis sometimes with iris atrophy Herpes Simplex Primary infection with the presence of a palpebral rash with a ''bouquet of flowers'' aspect, dendritic keratitis CMV Chorioretinitis with retinal hemorrhage giving the appearance of ''Cheese on Ketchup'' in a patient with HIV and having a CD4 lymphocyte count below 50/mm 3…”
Section: Herpes Zostermentioning
confidence: 99%
“…Medical virology has become particularly important in the past 30 years with the onset of the HIV / AIDS pandemic, recurrent episodes of fevers due to hemorrhagic viruses in Africa, and various outbreaks of SARS (severe acute respiratory syndrome) cases in Asia [1][2][3]. Once in the body, some of these viruses have an eye tropism.…”
Section: Introductionmentioning
confidence: 99%